1987
DOI: 10.1111/j.1475-1313.1987.tb00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Excursion Tests of Ocular Motility

Abstract: Three alternative excursion tests of ocular motility have been compared. A computer model of the mechanics of the extraocular muscles has been used to estimate the tensions developed by the muscles in these tests. On the basis of these calculations we recommend the transverse test in which the positions of the eyes are observed as they track a target moving from the right to the left with a fixed elevation and a fixed depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…1982). In other studies by Clement and Howrie (1985) and by Boylan and Clement (1987). V-and A-motility patterns and seceral tests of ocular motilitq ueie anal>zed Kault et a1 (i987) studied the influence of the Size ot the eqe.…”
Section: Introductionmentioning
confidence: 98%
“…1982). In other studies by Clement and Howrie (1985) and by Boylan and Clement (1987). V-and A-motility patterns and seceral tests of ocular motilitq ueie anal>zed Kault et a1 (i987) studied the influence of the Size ot the eqe.…”
Section: Introductionmentioning
confidence: 98%
“…This change was made Computed extraocular muscle activity during blinks: C . Boylan and R. A. Clement because the paths of the muscles are incorrect in the primary position in that the superior rectus passes underneath the superior oblique and the inferior rectus does not touch the inferior oblique (Boylan and Clement, 1987). Although this error does not significantly alter the calculated length changes of the muscles, it does lead to errors in the calculation of their secondary actions.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, Boylan and Clement (1987) used a description of the mechanical actions of the extraocular muscles to compare the effectiveness of excursion tests of oculomotility, and it was shown that the most effective test of the vertically acting muscles involves examining the eye during a transverse movement when they are elevated and when they are depressed. We have calculated the appearance of the eyes when each of the vertically acting muscles of the left eye have a 75% paresis and the right eye is fixating the outer points on the Hess screen, with -30,O and +30 degrees of horizontal movement.…”
Section: Interpretation Of Oculomotility Testsmentioning
confidence: 99%